The relationship between personality dimensions and employee job commitment in private higher learning institutions - Siti Aishah Berhan (2010)
Research on personality dimensions and employees' job commitment has not yet broad especially in the context of private higher learning institutions in Kota Kinabalu. Therefore, the objectives of this study are to examine the relationship between personality dimensions that affect job commitment and to determine whether gender differences and job level will influences employee job commitment. In this study, there are several aspects under personality dimensions that might be important in the area of employees' job commitment. According to the researcher's review on previous researches, there are few types of personality aspects that have been mentioned and explained. Among the types that might be contribute and could be relate to employee job commitment are extroversion, agreeableness, openness to experience, conscientiousness and neuroticism. In line with that, all the questionnaires have been analyzed by using the Statistical Package for Social Science (SPSS) and there are 144 respondents from managerial and non managerial level has been chosen to answer the question. After conducting this research through few analyses, only conscientiousness has significant relationship with job commitment. In this study also, one of the moderator which is the job level also indicate the significance relationship between personality dimensions and employees' job commitment.